Leveraging printability and biocompatibility in materials for printing implantable vessel scaffolds - Tianhong Chen; Haihong Jiang; Ruoxuan Zhang; Fan He; Ning Han; Zhimin Wang; Jia Jia (Materials Today Bio)
Vessel scaffolds are crucial for treating cardiovascular diseases (CVDs). It is currently feasible to fabricate vessel scaffolds from a variety of materials using traditional fabrication methods, but the risks of thrombus formation, chronic inflammation, and atherosclerosis associated with these scaffolds have led to significant limitations in the clinical usages. Bioprinting, as an emerging technology, has great potential in constructing implantable vessel scaffolds. During the fabrication of the constructs, the biomaterials used for bioprinting have offered significant contributions for the successful fabrications of the vessel scaffolds. Herein, we review recent advances in biomaterials for bioprinting implantable vessel scaffolds. First, we briefly introduce the requirements for implantable vessel scaffolds and its conventional manufacturing methods. Next, a brief overview of the classic methods for bioprinting vessel scaffolds is presented. Subsequently, we provide an in-depth analysis of the properties of the representative natural, synthetic, composite and hybrid biomaterials that can be used for bioprinting implantable vessel scaffolds. Ultimately, we underscore the necessity of leveraging biocompatibility and printability for biomaterials, and explore the unmet needs and potential applications of these biomaterials in the field of bioprinted implantable vessel scaffolds.